A systematic review of the supply of agriproducts to supermarkets in emerging markets of Africa and Asia - Abigail Oparebea Boateng; Richard Kwasi Bannor; Ebenezer Bold; Oppong-Kyeremeh Helena (Cogent Food & Agriculture, 2023)
AbstractThis paper systematically sheds light on the procurement systems, the selection criteria of Supermarket agrifood suppliers, and the impact of procurement systems on producers. A systematic search of literature from 2000 to 2022 was carried out. Fifty-two peer-reviewed research articles were identified from the Scopus database. The review findings revealed a positive impact on the income, productivity, and efficiency of the suppliers of supermarkets. Supermarkets used a combination of procurement systems (modernised and traditional) but primarily used the modernised method. Most studies reported that pricing and quality of food, the safety of produce, quantity, supply stability, delivery timeliness, and trust connections determine whether supermarkets buy from small or large producers. From the study, it is suggested that, to attract and maintain consumers in the underdeveloped areas, supermarket managers have to practice a just-in-time inventory management system where stocks will be kept low and also integrate vendor relationship management to reduce the cost of fresh fruits and vegetables sold at the Supermarket.